A Representação Social da Matemática em função do sexo e do gênero - Souza, Luciane Barboza de (2006)
The present study had as objective to investigate the social representations of the Mathematics in function of the sex and of the gender. The differences among the two terms are being proposed by researchers and professionals worried with the form by the which the individual differences are appraised. In fact, the sex has been predominantly used to describe differences between men and women with base in the biological aspect, while gender refers the one I correlate psychological. In that sense the individuals can be compared by the ownership of different indexes of manliness and femininity. It appears the interest then for the study of the social representations of the Mathematics, as area traditionally, and exclusively destined to the men and having a growing entrance of women, in the last decades, in graduation course. Using PAQ - personal attributes questionnaire, that assess the participants' level of masculinity and femininity, 152 university students of both sexes (76 men and 76 women, with medium age 21,57 years old, belonging to different courses of graduation of Mathematics of the state of Rio de Janeiro. The social representation of the Mathematics was considered previously starting from four dimensions established: affective, school, social and instrumental. The comparison with base in the sex, using the qui-square test, it allowed to identify differences significant frequency with that men and women represent the Mathematics in the four considered dimensions. The same happened in relation to the comparison starting from the masculinity (individuals with low and high masculinity degree). in relation to the femininity, however, they were not found significant differences. The data analysis allowed then identify the pertinence of analysis of the social representations of the Mathematics starting from the ownership of attributes considered as masculine or feminine, in spite of still there to be adaptation of the use of the sex as independent variable. There are pointed limitations of this study and suggestions for future studies.